1999
DOI: 10.2307/176919
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ecosystem Impacts of an Introduced Grass in the Northern Great Plains

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Introduced plants can have negative effects on native sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(142 citation statements)
references
References 39 publications
4
138
0
Order By: Relevance
“…Succession in our old field was accompanied by an increase in the cover of the introduced perennial grass Agropyron cristatum to 25%, suggesting that this old field is susceptible to invasion by nonnative species. In contrast, fields abandoned during the 1930s-1950s returned to dominance by native prairie (Judd 1940, Coffin et al 1996, Christian and Wilson 1999. The difference in the successional end points may have two causes: A. cristatum has been widely planted since the 1930s, so dispersal from planted stands into unplanted abandoned fields has increased over time, and the seed bank of native species probably had been extirpated by the time our field was abandoned (Bekker et al 1997, Wilson 2002.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Succession in our old field was accompanied by an increase in the cover of the introduced perennial grass Agropyron cristatum to 25%, suggesting that this old field is susceptible to invasion by nonnative species. In contrast, fields abandoned during the 1930s-1950s returned to dominance by native prairie (Judd 1940, Coffin et al 1996, Christian and Wilson 1999. The difference in the successional end points may have two causes: A. cristatum has been widely planted since the 1930s, so dispersal from planted stands into unplanted abandoned fields has increased over time, and the seed bank of native species probably had been extirpated by the time our field was abandoned (Bekker et al 1997, Wilson 2002.…”
Section: Discussionmentioning
confidence: 99%
“…We worked in Grasslands National Park (49Њ11Ј N, 107Њ43Ј W), about 140 km south of Swift Current, Saskatchewan, Canada. The natural vegetation of the region is mixed-grass prairie dominated by blue grama (Bouteloua gracilis), needle-and-thread grass (Stipa comata), and spikemoss (Selaginella densa; Christian and Wilson 1999). weather data from the nearest meteorological station (Val Marie, 10 km southeast; Environment Canada, unpublished data) showed that annual precipitation was 313 mm, with almost half falling during May-July.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it has been difficult to isolate the role of the vegetation factor in previous studies because they observed abandoned agricultural fields where vegetation colonization and succession dynamics are unavoidable (Odum 1960. Model results have suggested that certain invasive grasses have the potential to alter SOC content differently than native plants (Ogle et al 2004), and a study that compared converted and abandoned grass-lands with different vegetation composition found differences in ecosystem properties, including SOC, between grassland types (Christian and Wilson 1999).…”
Section: Introductionmentioning
confidence: 99%
“…One of the species most commonly used for restoration is the C 3 tussock grass Agropyron cristatum, native to Russia but planted on 6-10 ϫ 10 6 ha of the Great Plains (Lesica and DeLuca 1996) and on ϳ7.5 ϫ 10 6 ha of the US intermontane west during [1985][1986][1987] (Pyke 1990). Compared with similarly aged fields dominated by native prairie species, A. cristatum stands are characterized by low plant diversity and soils that are low in moisture, carbon, and nitrogen (Christian and Wilson 1999). Introduced grasses have also altered diversity and ecosystem function in Hawaii (D'Antonio and Vitousek 1992) and the intermontane west (Mack and Pyke 1984).…”
Section: Introductionmentioning
confidence: 99%